2016
DOI: 10.1111/nph.13882
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid regulates root growth under osmotic stress conditions via an interacting hormonal network with cytokinin, ethylene and auxin

Abstract: Summary Understanding the mechanisms regulating root development under drought conditions is an important question for plant biology and world agriculture.We examine the effect of osmotic stress on abscisic acid (ABA), cytokinin and ethylene responses and how they mediate auxin transport, distribution and root growth through effects on PIN proteins. We integrate experimental data to construct hormonal crosstalk networks to formulate a systems view of root growth regulation by multiple hormones.Experimental ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
200
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(219 citation statements)
references
References 99 publications
12
200
0
2
Order By: Relevance
“…S8). Blocking of ABA biosynthesis was reported to release inhibition of root growth under moderate osmotic stress (Rowe et al, 2016), supporting our finding that ABA is implicated in growth control during stress. Growth restriction during osmotic stress can be mediated by growth-repressing DELLA proteins, which are stabilized by ABA, but are promoted to degradation by gibberellins (Achard et al, 2006;Golldack et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…S8). Blocking of ABA biosynthesis was reported to release inhibition of root growth under moderate osmotic stress (Rowe et al, 2016), supporting our finding that ABA is implicated in growth control during stress. Growth restriction during osmotic stress can be mediated by growth-repressing DELLA proteins, which are stabilized by ABA, but are promoted to degradation by gibberellins (Achard et al, 2006;Golldack et al, 2013).…”
Section: Discussionsupporting
confidence: 79%
“…These results suggest that there is an intimate relationship among starvation, senescence-related pathways, and ABA signaling, which regulates responses to phosphate deficiency. ABA triggers defenses during drought or high-soil salinity and mediates growth inhibition (Finkelstein, 2013;Rowe et al, 2016). We found that on phosphate-deficient medium, rosette growth of the ABA deficient aba2-3 mutant was less reduced than wild type, suggesting that ABA is implicated in growth inhibition in such nutritional stress.…”
Section: Discussionmentioning
confidence: 77%
“…PIN1 , a gene encoding the auxin transporter, showed a decreased expression when osmotic stress was applied (Rowe et al, 2016). Salt stress disturbed the expression of the PIN genes and stabilized AXR3/IAA17, which in turn reduced the size of the root meristem because of the lower auxin level (Liu et al, 2015).…”
Section: Abi5 As the Integrator Of Aba And Other Phytohormone Signalimentioning
confidence: 99%
“…The influx and efflux carriers of the auxin transporter that are distributed in the plasma membrane are grouped into three major categories: auxin resistant 1/like aux1 (AUX1/LAX) influx carriers, P-glycoprotein (MDR/PGP/ABCB) efflux/conditional transporters, and plant specific PIN-FORMED (PIN) efflux carriers. The PINs are known as the most important auxin carriers that control the auxin PAT process (Péret et al, 2012; Adamowski and Friml, 2015; Yue et al, 2015; Row et al, 2016). Recently, PIN-LIKES (PILS) family, which are localized to the endoplasmic reticulum and involved in the regulation of intracellular auxin homeostasis, was characterized as a novel putative auxin carriers (Barbez et al, 2012; Feraru et al, 2012).…”
Section: Introductionmentioning
confidence: 99%